PENGARUH KEPRIBADIAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT BPR FAJAR ARTHA MAKMUR - Ilyas, Yasnimar; Zannah, Raudhatul (Economicus, 2018)
The purpose of this study was to determine the effect of personality and motivation on the performance of PT BPR Fajar Artha Makmur employees. In this study the object is a permanent employee or contract of PT BPR Fajar Artha Makmur. The population in this study were all employees working at the office of PT BPR Fajar Artha Makmur in the operational field of 50 people. The samples taken were 50 samples. Data analysis uses multiple linear regression. The results of the study showed discipline at PT. BPR Fajar Artha Makmur has gone very well. This can be seen based on the answers of 50 respondents, with an average number of 3.82. Motivation at PT. BPR Fajar Artha Makmur has gone quite well. This can be seen based on the answers of 50 respondents, with an average number of 3.02. Employee performance at PT. BPR Fajar Artha Makmur has gone well. This is seen based on the answers of the respondents as many as 50 people, with an average number of 3.05. Based on the results of data analysis using statistical methods, namely the correlation coefficient that is equal to 0.797, and according to the provisions of the author, it can be concluded that discipline and motivation have a strong level of relationship strength to employee performance variables, this shows that discipline and motivation have a strong influence on performance employees at PT. BPR Fajar Artha Makmur.